2013
DOI: 10.1371/journal.pone.0067582
|View full text |Cite
|
Sign up to set email alerts
|

2-phenylethynesulfonamide Prevents Induction of Pro-inflammatory Factors and Attenuates LPS-induced Liver Injury by Targeting NHE1-Hsp70 Complex in Mice

Abstract: The endotoxin-mediated production of pro-inflammatory cytokines plays an important role in the pathogenesis of liver disorders. Heat shock protein (Hsp70) overexpression has established functions in lipopolysaccharide (LPS)-mediated inflammatory response. However, little is known about the role of Hsp70 activity in LPS signaling. We hypothesized that inhibition of Hsp70 substrate binding activity can ameliorate LPS-induced liver injury by decreasing induction of pro-inflammatory factors. In this study, C57/BL6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…They also act on neurons with the assistance of endothelial cell transporters [6] . Our previous studies showed that pifithrin-μ attenuates the production of pro-inflammatory factors in both microglia and macrophages [14,15] , demonstrating that the anti-sickness effect of pifithrin-μ may be associated with its prevention on cytokine production. Reduction of food intake is one of the symptoms observed after the overproduction of pro-inflammatory cytokines in the innate immune system.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…They also act on neurons with the assistance of endothelial cell transporters [6] . Our previous studies showed that pifithrin-μ attenuates the production of pro-inflammatory factors in both microglia and macrophages [14,15] , demonstrating that the anti-sickness effect of pifithrin-μ may be associated with its prevention on cytokine production. Reduction of food intake is one of the symptoms observed after the overproduction of pro-inflammatory cytokines in the innate immune system.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, animals treated with pifithrin-μ prior to LPS administration displayed a decrease in serum corticosterone levels. Previous studies showed that pifithrin-μ exerts its pharmacological effects mainly through targeting the Hsp70 C terminal substrate binding activity [13] , and this targeting dissociates a battery of molecules such as apoptotic protease activating facter-1 (APAF1) and Na + /H + exchanger-1 from Hsp70 [13][14][15] . Hsp70 interacts physically with the intracellular glucocorticoid receptor (GR) and facilitates its activation by glucocorticoids [22,23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NHE1 and HSP70 were previously shown to interact in PS127A Chinese hamster fibroblasts [17]. More recently [41], HSP70 was found to be dynamically associated with NHE1 in macrophages. Heat shock proteins are inducible molecular chaperones that facilitate the folding of proteins and their transport across membranes, and prevent protein aggregation in response to cellular stress.…”
Section: Nhe1 and Chaperone Proteinsmentioning
confidence: 99%
“…Similarly, increases in macrophage phagocytosis and neutrophil microbicide activity have been reported after exogenous Hsp70 administration (Kovalchin et al, 2006; Ortega et al, 2006). eHsp70 also prompted pro-inflammatory cytokine release from epithelial, innate immune and adaptive immune cells, which may explain why eHsp70 is associated with inflammatory cytokine production in multiple mouse and human studies (Asea et al, 2000; Asea et al, 2002; Basu et al, 2001; Chase et al, 2007; Dvoriantchikova et al, 2014; Dybdahl et al, 2005; Huang et al, 2013; Qiao et al, 2008). Collectively, these data support a strong capacity of eHsp70 to initiate and escalate an immune-mediated inflammatory response.…”
Section: 0– Extracellular Hsp70mentioning
confidence: 99%